Техніко-економічне обґрунтування ефективності використання гвинтових змішувачів - Гевко, І. Б.; Гупка, А. Б.; Коваль, С. О.; Брикса, А. О.; Бучинський, В. М.; Нevko, I.; Gupka, A.; Koval, S.; Briksa, A.; Buchynsky, V. (ЦНТУ, 2025)
Проведено техніко-економічне обґрунтування ефективності використання гвинтових змішувачів трьох типів за умови досягнення ними однакової якості змішування. Встановлено, що гвинтовий змішувач з обертовим кожухом є найбільш економічно ефективним і може забезпечувати отримання найнижчої неоднорідності суміші за найнижчих витрат. Витрати на змішування при його застосуванні є в 1,09 рази нижчими, ніж при її змішуванні гвинтовим жорстким транспортером-змішувачем, і в 3,41 рази нижчими, ніж при її змішуванні гвинтовим змішувачем з пересипом. Встановлено, що для досягнення високої якості змішування суміші жорсткими гвинтовими конвеєрами-змішувачами існують підвищені витрати на їх виготовлення та експлуатацію, пов’язані із значною довжиною траси перелопачування суміші, а у шнекових змішувачах з пересипанням існують підвищені витрати на електроенергію, враховуючи необхідність здійснення значної кількості циклів для перелопачування суміші, а також часто неможливість переміщення суміші в потрібному напрямку. Screw transport and technological mechanisms have gained the greatest use as conveyors and mixers of materials. This combination of processes allows for the use of one mechanism instead of two. However, the intensity of mixing in such tools is not always high. Therefore, often, in order to obtain the required quality, a significant number of shoveling of the mixture is required, which requires either an increase in the length of the technical means, or ensuring the cyclical operation of it. Therefore, the purpose of the work is to carry out a technical and economic substantiation of the feasibility of using screw conveyors-mixers with rotating casings. An important task of their research was to find ways to ensure the quality of mixing of loose components due to the development and modernization of original designs of screw conveyors-mixers. In order to ensure significant productivity of the transport and technological process of transportation and the quality ofmixing of loose materials, the design of a screw conveyor-mixer with a rotating casing was developed, patented and researched. In the existing designs of screw mixers, high quality mixing can be obtained either due to a significant length of mixing, or due to the cyclic mode of operation, which does not ensure the movement of materials etc.
Technical and Economic Substantiation of the Effectiveness of the Use Of Screw Mixers
Keywords: гвинтовий конвеєр-змішувач; обертовий кожух; продуктивність; неоднорідність суміші; техніко-економічне обґрунтування; screw conveyor-mixer; rotary casing; performance; mixture heterogeneity; feasibility study